Foliar spray of mineral nutrients enhanced the growth, seed yield, and quality in onion (Allium cepa L.) cv. Pusa Riddhi. (28th May 2018) - Kumar, Sanjay; Tomar, B. S.; Saharawat, Y. S.; Arora, Ajay
ABSTRACT: The present experiment was conducted to investigate the effect of foliar spray of mineral nutrients on plant growth, seed yield, and quality attributes in onion cv. Pusa Riddhi at SPU, IARI, New Delhi during rabi 2013–14 and 2014–15. The experiment consisted of 16 treatments comprised of boron, zinc, calcium, and magnesium laid out in a completely randomized block design with two replications. The study revealed that the foliar zinc spray (625 g ha −1 ) produced higher seed scape height (105.35 cm) along with lower disease incidence (8.50%) than the other treatments. Whereas, higher number of seed scapes plant −1 (11.20) and productive seed scapes plant −1 (8.58) were observed in T10 (500 g ha −1 ) and combined spray of B + Zn + Ca (T14 ), respectively. The flowering traits, viz., umbellates umbel −1 (642.45), productive umbellates umbel −1 (579.35), and umbel diameter (7.38cm) were significantly ( p ≤ 0.05) higher in T15 than other treatments. Similarly, higher seed yield and seed quality attributes were also observed in combined application of all minerals treatment (T15 ).